The Impact of Applying the Total Quality Management and Kaizen Methods on the Maintenance of Electricity and Water sectors - Al-Juboori, Salloom A.; Al-Azemi, Fawaz A. (European Scientific Journal, ESJ, 2016)
In this work the total quality management (TQM) and Kaizen philosophies were applied on the electricity and public water sector maintenance. The methodology of collecting the data was by designing a special questionnaire containing a series of questions comparing these two philosophies for a specific period of application to study their effect on the maintenance and the cost in the electricity and public water sector. After six months of applying these philosophies, the questionnaire data were collected and analyzed using SPSS package. The results have shown that 55% of employees believe that the philosophy of kaizen is relatively applied in the electricity sector. But there is a ratio of 65% of them think that the administration of the total quality management is the most suitable to be applied in the electricity and water sectors. In addition to that there is a ratio of about 50% see that both methods have achieved better improvements of maintenance in comparison with traditional methods, consequently both methods were successful in the electricity sector for improving maintenance and reducing the cost. But the results were almost equal and this may indicate that due to the lack of sufficient knowledge of the pros and cons of both ways.